(untitled) (Human Geographies – Journal of Studies and Research in Human Geography, 2025)
Areal differentiation is one of the critical and traditional concepts in geographical studies, reconsidered through the philosophy of Deleuze in the present article. It has been argued that geographical areas should be conceptualised as virtual entities whose source of differentiation rises from their internal force. The paper argues that geographers have access to the virtual entities only in the public words and ideas, tending to naturalise one image while excluding others and advocating particular power relations between different human/non-human elements in an area. Finally, it has been discussed that one of the main tasks of human geographers is to uncover naturalised images about the process of areal differentiation. It entails considering human geography as an artistic practice instead of scientific activity. When geographers-artists select an image of areal differentiation, they should be open to replacing it with new alternative images.